PENGEMBANGAN TEPUNG IKAN PATIN DAN BAYAM SEBAGAI BAHAN SUBTITUSI BISKUIT UNTUK FINGER FOOD PADA BALITA - Pitriyah, Nurul; Mashar, Harlyanti Muthma'innah; Wardani, Rizky Kusuma; Dali, Dali; Sukrianur, Ahmad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Low or poor nutritional status in the growth of infants and children, namely at the age of under five years, can result in impaired physical growth and intelligence. Rapid brain development can only be achieved if the child has good nutritional status. Children given complementary foods after 6 months are generally smarter and have stronger immune systems, reducing the risk of food allergies. The research design was a completely randomized design using three variations of the formula comparison of catfish flour: spinach flour: wheat flour, P1 (15 g: 45 g: 240 g), P2 (30 g: 30 g: 240 g), and P3 (45 g: 15 g: 240 g). Then organoleptic and acceptability tests were carried out. The results showed that the characteristics of catfish flour have a brownish white color, a fishy aroma of catfish, a slightly rough texture, and a slightly lumpy texture. Spinach flour is bright green, has a powerful spinach aroma, a smooth texture, and does not lump. Biscuit products have characteristics of green color, savory taste, crunchy texture, and aroma not typical of catfish. The acceptance test results showed that 30 panelists liked the flavor and smell of formula P2, while the texture and color were like formula P3.